Determinants of Employee Performance at the Sungai Penuh City Health Office: Mediation of Organizational Citizenship Behavior - Sumiati Sumiati; Zusmawati Zusmawati; Maria Magdalena; Saiful Anwar; Era Syafitri; Heriyandi Heriyandi (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study analyzes the effect of job satisfaction and organizational commitment on employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable at the Sungai Penuh City Health Office. A quantitative explanatory design was applied using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS 3.0. The study involved all 47 employees through a census method. The results show that job satisfaction and organizational commitment have positive and significant effects on OCB and employee performance. OCB also has a direct significant effect on performance and mediates the influence of job satisfaction and organizational commitment on employee performance. These findings indicate that OCB functions as a strategic mechanism that translates positive employee attitudes into improved work outcomes. Practically, the results suggest that management should enhance job satisfaction through fair compensation, supportive work environments, recognition systems, and career development opportunities. Strengthening organizational commitment through transparent communication, employee involvement in decision-making, and reinforcement of organizational values is equally essential. Additionally, fostering a work culture that encourages voluntary behaviors such as teamwork, initiative, and mutual support can promote sustainable performance improvement. Integrating these strategies is crucial for improving service effectiveness and strengthening organizational performance in the public health sector.This study analyzes the effect of job satisfaction and organizational commitment on employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable at the Sungai Penuh City Health Office. A quantitative explanatory design was applied using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS 3.0. The study involved all 47 employees through a census method. The results show that job satisfaction and organizational commitment have positive and significant effects on OCB and employee performance. OCB also has a direct significant effect on performance and mediates the influence of job satisfaction and organizational commitment on employee performance. These findings indicate that OCB functions as a strategic mechanism that translates positive employee attitudes into improved work outcomes. Practically, the results suggest that management should enhance job satisfaction through fair compensation, supportive work environments, recognition systems, and career development opportunities. Strengthening organizational commitment through transparent communication, employee involvement in decision-making, and reinforcement of organizational values is equally essential. Additionally, fostering a work culture that encourages voluntary behaviors such as teamwork, initiative, and mutual support can promote sustainable performance improvement. Integrating these strategies is crucial for improving service effectiveness and strengthening organizational performance in the public health sector.